50.0k views
5 votes
Solve for x
3x - 5 (x-4) = -6

User Mlemos
by
6.2k points

2 Answers

3 votes
  1. Foil -5(x - 4):
    3x-5x+20=-6
  2. Combine like terms:
    -2x+20=-6
  3. Subtract 20 on both sides:
    -2x=-26
  4. Lastly, divide both sides by 2, and your answer will be
    x=13
3 votes

3x - 5(x - 4) = -6

  • Distribute 5 inside the parentheses.

3x - 5x + 20 = -6

  • Combine like terms.

-2x + 20 = -6

  • Subtract 20 from both sides.

-2x = -26

  • Divide both sides by -2.

x = 13

  • is your answer.
User Taxicala
by
5.6k points